Impact of menopause hormone therapy, exercise, and their combination on bone mineral density and mental wellbeing in menopausal women: a scoping review - Olivia Platt; Olivia Platt; James Bateman; James Bateman; Shagaf Bakour; Shagaf Bakour; Shagaf Bakour (Frontiers in Reproductive Health)
BackgroundOsteoporosis, a condition marked by low bone mineral density (BMD) and structural deterioration, affects more women than men over 50 globally. In women, declining estrogen during the menopause accelerates bone resorption, heightening fracture risk. An association between osteoporosis and depression, frailty fractures and poor quality of life has been identified. Both menopause hormone therapy (MHT) and exercise are shown to improve BMD, with MHT reducing bone resorption and exercise promoting bone formation. This review examines the effectiveness of MHT, exercise, and their combination in managing menopausal osteoporosis.MethodA multifactor scoping review was conducted to address osteoporosis and MHT, osteoporosis and exercise, and osteoporosis and MHT and exercise combined.ResultsInitial searches identified 15,158 studies, narrowed to 20 meeting the inclusion criteria. MHT and exercise are effective in preserving BMD in menopausal women. Combined estrogen and progesterone MHT is more effective than estrogen-only, with studies suggesting that MHT prescribed at low doses for longer durations more effectively preserves BMD. Resistance training (RT) completed 2–3 days per week at a moderate-to-high intensity combined with impact activity completed at a minimum of 3 days per week is optimal for improving BMD in menopausal women, while low-impact exercises provide supplemental benefits. Combining MHT with exercise enhances BMD more than either alone.ConclusionThis review highlights that combining MHT and structured exercise is most effective for enhancing BMD in menopausal women. Given certain safety considerations surrounding MHT in some women, exercise remains a cornerstone for the prevention and management of osteoporosis as well as for promoting overall wellness.